Myosin 1g Contributes to CD44 Adhesion Protein and Lipid Rafts Recycling and Controls CD44 Capping and Cell Migration in B Lymphocytes - López-Ortega, Orestes; Santos-Argumedo, Leopoldo (Frontiers in Immunology, 2017)
Cell migration and adhesion are critical for immune system function and involve many proteins, which must be continuously transported and recycled in the cell. Recycling of adhesion molecules requires the participation of several proteins, including actin, tubulin, and GTPases, and of membrane components such as sphingolipids and cholesterol. However, roles of actin motor proteins in adhesion molecule recycling are poorly understood. In this study, we identified myosin 1g as one of the important motor proteins that drives recycling of the adhesion protein CD44 in B lymphocytes. We demonstrate that the lack of Myo1g decreases the cell-surface levels of CD44 and of the lipid raft surrogate GM1. In cells depleted of Myo1g, the recycling of CD44 was delayed, the delay seems to be caused at the level of formation of recycling complex and entry into recycling endosomes. Moreover, a defective lipid raft recycling in Myo1g-deficient cells had an impact both on the capping of CD44 and on cell migration. Both processes required the transportation of lipid rafts to the cell surface to deliver signaling components. Furthermore, the extra membrane was essential for cell expansion and remodeling of the plasma membrane topology. Therefore, Myo1g is important during the recycling of lipid rafts to the membrane and to the accompanied proteins that regulate plasma membrane plasticity. Thus, Myosin 1g contributes to cell adhesion and cell migration through CD44 recycling in B lymphocytes.